MASCO Industries Limited (A concern of MASCO Group) Kendua, Kanchan, Rupganj, Narayanganj - Islam, Md. Tauhidul (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Post Graduate Diploma in Knitwear Industry Management, 2019.